UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU EKONOMI DALAM MENGHADAPI ERA PENDIDIKAN 4.0 DI KOTA PADANG - OKNARYANA, OKNARYANA; MARNA, JEAN ELIKAL; ZULVIA, YOLANDAFITRI (Manajemen dan Kewirausahaan, 2020)
The 4.0 industrial revolution was first introduced in Germany in 2011. This revolution combines automation technology with cyber technology. With the advent of this revolution the level of competition is getting tougher. Therefore, Human Resources (HR) itself must be able to compete to survive in this 4.0 era. One improvement of HR can be done through education. Education 4.0 is the integration of cyber technology or the internet of things into the world of education. The spearhead of education is the teacher. In the face of this 4.0 education, teachers must be able to use cyber technology in pedagogical abilities. Pedagogical ability is the ability of students' understanding, design, implementation and evaluation of student learning outcomes. This research is a descriptive study and was conducted on teachers who joined the MGMP of Economics teachers in Padang City. This research was conducted to see the teacher's pedagogical ability in facing the era of education 4.0. From the results of the questionnaire distributed the average teacher's pedagogical ability in the good category with an average value of 76.72.